PELAKSANAAN MANAJEMEN PROGRAM GERAKAN MASYARAKAT MAGRIB MENGAJI DI PROVINSI SUMATERA BARAT STUDY KOMPARATIF DI TIGA DAERAH - Delfi Indra (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Program Manajement Implementation Magrib Koran In West Sumatra province. Thepurpose of this study was to determine the Implementation of Program Management SocietyMovement Maghrib Koran in the province of West Sumatra in Jorong Gantiang Nagari PadangMagek Tanah Datar District of propagation, Jorong Nagari Koto Baru Bukit Kili lemur District ofSolok District and Village Laing Solok District of Cape of Good Hope. The research method I use isQualitative data collection techniques (1) Observation, (2) Interview and (3) Study of Documentation.The data were analyzed by means of data reduction, data presentation and inclusion.The results of this study were (1) Management of the program sunset Koran society movements in thethree regions are very different in practice, it looks at Jorong Gantiang have excellent management,Jorong Bukit Kili implement the program management has not been as good and Laing Villagemanagement has yet to implement this program as it should, it looks a lack of support from thetown and village governments (2) Activities conducted in community programs dusk chantingmovement is also different in each of these areas, in Jorong Gantiang there are 10 activities performedby generating a characteristic regions such as customary speech Pasambahan, in Bukit Kili Jorong no7 Sub Laing activity while only 5 activity. and that (3) The effect that appears to the public is alsodifferent in the three regions, as in Jorong Gantiang communities already praying in congregationin Mushalla Nurul Hidayah and their home each with their own awareness, while the MountKili community Jorong sunset prayers in congregation in the Masjid Al-Ikhwan and implementprogram activities in the dusk Koran, and the Village Laing has not appeared influence on societyThe conclusion of this study is necessary active role of all components of society that exist in everyregion in the implementation of this Koran dusk society movement, especially in the area being builtin this program. This study also gives the meaning, especially in the province of West Sumatra, sothis program really accomplished in accordance with the expectations of society and government.Kata Kunci: Manajemen, gerakan masyarakat, maghrib mengaji